2020
DOI: 10.1177/1934578x20904497
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Total Saponins From Dioscorea nipponica Makino on Gouty Arthritis Based on the MAPK-PPARγ Signaling Pathway: An In Vitro Study

Abstract: Gouty arthritis (GA) is an inflammatory disease caused by the deposition of monosodium urate in the synovial membrane and cartilage due to a high concentration of uric acid in the blood. Dioscorea nipponica Makino is widely used in the clinic to treat GA. Total saponins are its main components and showed an anti-inflammatory effect on GA in a previous study. The mitogen-activated protein kinase (MAPK)-peroxisome proliferator-activated receptor γ (PPARγ) signaling pathway plays a key role during the onset of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…AdipoR2 mRNA levels; however, AdipoR2 protein levels did not differ compared with the control group. The result is quite consistent with our in vitro study [20]. This finding may be explained by the self-recovery features of GA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…AdipoR2 mRNA levels; however, AdipoR2 protein levels did not differ compared with the control group. The result is quite consistent with our in vitro study [20]. This finding may be explained by the self-recovery features of GA.…”
Section: Discussionsupporting
confidence: 93%
“…To protect the animals, ethical approval for the experiments was obtained based on the Legislation on the Protection of Animals Used for Experiment Purposes (Directive 86/609/EEC). The Institutional Animal Care Committee approved the experiment (approval number was 20,190,921).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying molecular mechanism may be that dioscin reduces inflammation by reducing the production of pro-inflammatory cytokines and inhibiting the activation of inflammasome NLRP3 and Toll-like receptor 4 (TLR 4)/NF-κB signaling pathway [ 80 ]. In addition, in vivo studies in mice with GA found that total yam saponins, the main components of which are dioscin, protodioscin, and pseudo protodioscin, exert anti-inflammatory effects for GA by regulating the expression of some key genes in the neutrophilic alkaline phosphatase-3 (NALP3), caspase-1, apoptosis-associated speck-like (ASC), and mitogen-activated protein kinase (MAPK)-peroxisome proliferator-activated receptor γ (PPARγ) signaling pathways [ 81 , 82 ]. Diosgenin from Dioscorea nipponica Makino had a therapeutic effect on collagen-induced arthritis in mice.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%